A compact and cost-effective laser desorption source for molecular beam generation: comparison with simulations. (30th September 2021) - Shachar, Afik; Kallos, Itai; de Vries, Mattanjah S; Bar, Ilana
Abstract: The development of laser-desorption jet-cooling has enabled the study of low vapor pressure molecules in the gas phase. Here, we design and assemble a unique compact laser-desorption source comprising simple parts for sample movement and desorption and attach it to a home-built time-of-flight mass spectrometer for spectroscopic studies of jet-cooled biomolecules. Modeling and visualization of the molecular beam (MB) by the direct simulation Monte Carlo method provides spatial evolution and global features of the flow and new insights into source operation. The system is validated by determining operational parameters from the simulation and comparing them with the resulting resonance-enhanced two-photon ionization (R2PI) signal of tryptamine. The signal measurements in the origin band transitions region provide an R2PI spectrum resembling that previously acquired from heated samples, indicating seven conformers in the MB. Due to the potential of this source, we expect that it will reveal its feasibility through coupling to other systems and various spectroscopies.